The Tapper twins go to war (with each other) / 1. - Rodkey, Geoff, 1970- (Rodkey, Geoff, 1970- Tapper twins, 2016)
An oral history that reports, through transcribed recordings, text messages, photographs, illustrations, screenshots, and more, an epic prank war between twelve-year-old twins Reese and Claudia Tapper of New York City.